Hop-stabilization training and landing biomechanics in athletes with chronic ankle instability: A randomized controlled trial - Karimizadeh Ardakani, M.; Wikstrom, E. A.; Minoonejad, H.; Rajabi, R.; Sharifnezhad, A. (Journal of Athletic Training, 2019)
Context: Hopping exercises are recommended as a functional training tool to prevent lower limb injury, but their effects on lower extremity biomechanics in those with chronic ankle instability (CAI) are unclear.